Analysis Of Priority Factors Affecting The Problems Of Waste Management System In Margasari, Balikpapan City - Noor Hayati, Rina; Devi Triwidya Sitaresmi (Journal of Multidisciplinary Science, 2022)
Margasari Village has different regional characteristics, the difference in the characteristics of the area causes differences in the waste management system in Margasari Village between land and water areas, resulting in differences in waste management methods and techniques. This study aims to determine the factors that influence the problem of solid waste management systems in land and water areas that cause it is not achieved optimally, using the Analytical Hierarchy Process (AHP) method. After the data processing and analysis were carried out, the factors that influenced the solid waste management system problems in Margasari Village were based on the components of the solid waste management system, namely operational techniques, institutions, financing, law and regulation, community roles and physical conditions, so that the results of the waste management system priority factors in Margasari Village, namely in the mainland area, the Community Role Indicator has a weight value of 0.29, and the priority weight of the Waste The processing variable has a weight value of 0.100 which is a variable that affects the problem of Community Roles in the Solid Waste Management System in Land Areas. Meanwhile, in the area over water, the Community Role Indicator has a weight value of 0.31 with a priority weight of the influencing variable Waste Processing with a weight value of 0.093.